IMPROVEMENT OF ABILITY OF MATHEMATICAL PROBLEM STUDY USING PROBING PROMPTING TECHNIQUE ASSISTED BLENDED LEARNING IN UNIVERSITY PGRI PALEMBANG - Rahmawati Rahmawati; Jayanti Jayanti (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to examine the improvement of Mathematical Problem Solving (KPMM) of students through Probing Prompting learning technique. Probing Prompting technique is learning by way of presenting a series of questions that are guided and explored so that there is a process of thinking that links the previous knowledge and experience with new knowledge to be learned. Questions raised on the students encourage students to think more rationally about the knowledge gained previously. In the face-to-face study dikuliah Differential Equation, assisted blended learning is by using the internet online. This study used quasi-experimental method with the control group design of pretest and non-equivalent postes. The subject of this research is a mathematics student at PGRI University of Palembang. namely experimental class that get learning Probing prompting assisted blended learning (PPPBBL) and control class that get conventional learning (PK). Based on the result of the test analysis, the difference of the average increase of KPMM of the students who get the learning PPPBBL and the students who get conventional learning, get the value of the table of the increase of KPMM students who get learning Prompting blended learning promotion (PPPBBL) better than students who get conventional learning